Make a system with 3 equations and 3 unknowns of which the solution space V is spanned by the column vectors: $$\left[\begin{array}{c}1\\ 0\\ -1\end{array}\right],\phantom{\rule{1em}{0ex}}\left[\begin{array}{c}1\\ 3\\ 0\end{array}\right]$$

Damon Vazquez
2022-09-06
Answered

Make a system with 3 equations and 3 unknowns of which the solution space V is spanned by the column vectors: $$\left[\begin{array}{c}1\\ 0\\ -1\end{array}\right],\phantom{\rule{1em}{0ex}}\left[\begin{array}{c}1\\ 3\\ 0\end{array}\right]$$

You can still ask an expert for help

Emilia Boyle

Answered 2022-09-07
Author has **10** answers

First of all, every equation system can be written as $AX=b$. The solution space is a vector space only if it is the $ker(A)$ which is a solution space of a system $AX=0$. In general the solution space is nothing but a coset of the $ker(A)$ (and the coset is not vector space unless it is equal to $ker(A)$.

So what you need now is just to find a matrix whose kernel is $V=\u27e8{v}_{1},{v}_{2}\u27e9$

We have $3$ variables, and solution space has two independent generators (in other words there are two free variables). Hence the solution space is a solution to only $one$ equation with $3$ variables. That means the other two equations should be just multiple of the first equation. Now to find the first equation we use the Gauss elimination method, but in reverse. To do this efficiently we need to bring the generating system to the form $\{(0,number,1),(1,number,0)\}$ ...etc.

To do this we can apply the elementary operations on the generators.

- Multiply one of them by a number and adding the result to another generator.

- Multiply or divide one of them by nonzero number.

For example, if

$$V=\u27e8{u}_{1}=(2,3,4),{u}_{2}=(1,2,3)\u27e9$$We multiply ${u}_{2}$ by $-2$ and add it to ${u}_{1}$, we get

$$V=\u27e8{u}_{3}=(0,-1,-2),{u}_{2}=(1,2,3)\u27e9$$

Now multiply ${u}_{3}$ with $-1$.

$$V=\u27e8{u}_{4}=(0,1,2),{u}_{2}=(1,2,3)\u27e9$$

We multiply ${u}_{4}$ by $-2$ and add it to ${u}_{2}$, we get

$$V=\u27e8{u}_{4}=(0,1,2),{u}_{5}=(1,0,-1)\u27e9$$

The system is now ready for revers Gause Elimination method. The generators in your question is much easier, and we need only to multiply by $\frac{1}{3}$ and $-1$.

The rest is easy as follows

$\begin{array}{ccc}V& =& \u27e8(1,3,0),(1,0,-1)\u27e9\\ & =& \u27e8(\frac{1}{3},1,0),(-1,0,1)\u27e9\\ & =& \{y(\frac{1}{3},1,0)+z(-1,0,1)|y,z\in \mathbb{R}\}\\ & =& \{(\frac{1}{3}y-z,y,z)|y,z\in \mathbb{R}\}\\ & =& \{(x,y,z)|x-\frac{1}{3}y+z=0,x,y,z\in \mathbb{R}\}\end{array}$

So the system desired can be for example:

$\left(\begin{array}{ccc}1& -\frac{1}{3}& 1\\ 3& -1& 3\\ 6& -2& 6\end{array}\right)$

Note that the rank of this matrix is $$1$$, therefore the dimension of the solution space is $$2$$, and ${v}_{1},{v}_{2}\in $ Solution Space, and they are linear independent, so the Solution Space is $V$.

So what you need now is just to find a matrix whose kernel is $V=\u27e8{v}_{1},{v}_{2}\u27e9$

We have $3$ variables, and solution space has two independent generators (in other words there are two free variables). Hence the solution space is a solution to only $one$ equation with $3$ variables. That means the other two equations should be just multiple of the first equation. Now to find the first equation we use the Gauss elimination method, but in reverse. To do this efficiently we need to bring the generating system to the form $\{(0,number,1),(1,number,0)\}$ ...etc.

To do this we can apply the elementary operations on the generators.

- Multiply one of them by a number and adding the result to another generator.

- Multiply or divide one of them by nonzero number.

For example, if

$$V=\u27e8{u}_{1}=(2,3,4),{u}_{2}=(1,2,3)\u27e9$$We multiply ${u}_{2}$ by $-2$ and add it to ${u}_{1}$, we get

$$V=\u27e8{u}_{3}=(0,-1,-2),{u}_{2}=(1,2,3)\u27e9$$

Now multiply ${u}_{3}$ with $-1$.

$$V=\u27e8{u}_{4}=(0,1,2),{u}_{2}=(1,2,3)\u27e9$$

We multiply ${u}_{4}$ by $-2$ and add it to ${u}_{2}$, we get

$$V=\u27e8{u}_{4}=(0,1,2),{u}_{5}=(1,0,-1)\u27e9$$

The system is now ready for revers Gause Elimination method. The generators in your question is much easier, and we need only to multiply by $\frac{1}{3}$ and $-1$.

The rest is easy as follows

$\begin{array}{ccc}V& =& \u27e8(1,3,0),(1,0,-1)\u27e9\\ & =& \u27e8(\frac{1}{3},1,0),(-1,0,1)\u27e9\\ & =& \{y(\frac{1}{3},1,0)+z(-1,0,1)|y,z\in \mathbb{R}\}\\ & =& \{(\frac{1}{3}y-z,y,z)|y,z\in \mathbb{R}\}\\ & =& \{(x,y,z)|x-\frac{1}{3}y+z=0,x,y,z\in \mathbb{R}\}\end{array}$

So the system desired can be for example:

$\left(\begin{array}{ccc}1& -\frac{1}{3}& 1\\ 3& -1& 3\\ 6& -2& 6\end{array}\right)$

Note that the rank of this matrix is $$1$$, therefore the dimension of the solution space is $$2$$, and ${v}_{1},{v}_{2}\in $ Solution Space, and they are linear independent, so the Solution Space is $V$.

asked 2022-06-20

Solving simultaneous equations with 3 parts

$\begin{array}{rl}2{x}^{2}+3y+z& =8\\ x-2y& =4\\ 3z-x& =7\end{array}$

$\begin{array}{rl}2{x}^{2}+3y+z& =8\\ x-2y& =4\\ 3z-x& =7\end{array}$

asked 2022-06-15

How to Find the all integer solutions for:

$x+y+z=3$

${x}^{3}+{y}^{3}+{z}^{3}=3$

$x+y+z=3$

${x}^{3}+{y}^{3}+{z}^{3}=3$

asked 2022-06-15

solve the following linear system

${x}_{1}-3{x}_{2}+{x}_{3}=1$

$2{x}_{1}-{x}_{2}-2{x}_{3}=2$

${x}_{1}+2{x}_{2}-3{x}_{3}=-1$

by using gauss-jordan elimination method. The augmented matrix of the linear system is

$\left(\begin{array}{cccc}1& -3& 1& 1\\ 2& -1& -2& 2\\ 1& 2& -3& -1\end{array}\right).$

By a series of elementary row operations, we have

$\left(\begin{array}{cccc}1& -3& 1& 1\\ 0& 5& -4& 0\\ 0& 0& 0& -2\end{array}\right).$

My question is, although the question asked us to solve the linear system using gauss-jordan elimination method, can we stop immediately and conclude that the linear system is inconsistent without further apply any elementary row operation to the matrix

$\left(\begin{array}{cccc}1& -3& 1& 1\\ 0& 5& -4& 0\\ 0& 0& 0& -2\end{array}\right)$

until the matrix

$\left(\begin{array}{cccc}1& -3& 1& 1\\ 0& 5& -4& 0\\ 0& 0& 0& -2\end{array}\right)$

is transformed into reduced-row echelon form?

${x}_{1}-3{x}_{2}+{x}_{3}=1$

$2{x}_{1}-{x}_{2}-2{x}_{3}=2$

${x}_{1}+2{x}_{2}-3{x}_{3}=-1$

by using gauss-jordan elimination method. The augmented matrix of the linear system is

$\left(\begin{array}{cccc}1& -3& 1& 1\\ 2& -1& -2& 2\\ 1& 2& -3& -1\end{array}\right).$

By a series of elementary row operations, we have

$\left(\begin{array}{cccc}1& -3& 1& 1\\ 0& 5& -4& 0\\ 0& 0& 0& -2\end{array}\right).$

My question is, although the question asked us to solve the linear system using gauss-jordan elimination method, can we stop immediately and conclude that the linear system is inconsistent without further apply any elementary row operation to the matrix

$\left(\begin{array}{cccc}1& -3& 1& 1\\ 0& 5& -4& 0\\ 0& 0& 0& -2\end{array}\right)$

until the matrix

$\left(\begin{array}{cccc}1& -3& 1& 1\\ 0& 5& -4& 0\\ 0& 0& 0& -2\end{array}\right)$

is transformed into reduced-row echelon form?

asked 2022-11-04

Solve for x

$$|x-1{|}^{\mathrm{log}(x{)}^{2}}-2\mathrm{log}(x))=|x-1{|}^{3}$$

$$|x-1{|}^{\mathrm{log}(x{)}^{2}}-2\mathrm{log}(x))=|x-1{|}^{3}$$

asked 2022-03-20

Solve $0.6-3.2x>-1.4-2.8x$ .

a.$x>5$

$b.x>10$ c.$5>x$

d.$x>1.62$

a.

d.

asked 2022-06-25

Solving system of multivariable 2nd-degree polynomials

$\begin{array}{c}{x}^{2}+3xy-9=0\phantom{\rule{1em}{0ex}}(1)\\ 2{y}^{2}-4xy+5=0\phantom{\rule{1em}{0ex}}(2)\end{array}$

where $(x,y)\in {\mathbb{C}}^{2}$.

More generally, how would you solve any set of equations of the form:

$\begin{array}{c}{ax}^{2}+bxy+c=0\\ d{y}^{2}+exy+f=0\end{array}$

where $a,b,c,d,e,f\in \mathbb{Q}$ and $(x,y)\in {\mathbb{C}}^{2}$.

$\begin{array}{c}{x}^{2}+3xy-9=0\phantom{\rule{1em}{0ex}}(1)\\ 2{y}^{2}-4xy+5=0\phantom{\rule{1em}{0ex}}(2)\end{array}$

where $(x,y)\in {\mathbb{C}}^{2}$.

More generally, how would you solve any set of equations of the form:

$\begin{array}{c}{ax}^{2}+bxy+c=0\\ d{y}^{2}+exy+f=0\end{array}$

where $a,b,c,d,e,f\in \mathbb{Q}$ and $(x,y)\in {\mathbb{C}}^{2}$.

asked 2021-09-06

Solve the system of equations by hand.